Pertanggungjawaban Hukum Pemerintah Desa dalam Pelayanan Publik kepada Masyarakat - Tarman Tarman; Mansyur Mansyur; Wawan Wawan; Muhamad Jamalih (Journal of Innovative and Creativity, 2025)
Public service is one of the main functions of village government as the leading governmental organization that directly relates to the community. This study examines "Legal Accountability of Village Government in Public Services to the Community" with the aim of understanding the form, mechanism, and scope of legal accountability inherent in village government when carrying out public services. Through a normative juridical approach by examining related laws and regulations, such as Law Number 6 of 2014 concerning Villages, Law Number 25 of 2009 concerning Public Services, and other technical regulations, this study found that village governments bear legal responsibility both administratively, civilly, and criminally for actions and decisions that cause harm to the community. This accountability encompasses aspects of legality of actions, compliance with service standards, transparency, and accountability in the use of authority. The research findings indicate that there are still obstacles in implementing accountability mechanisms, such as low understanding among village officials, minimal oversight, and weak documentation of service procedures. This study recommends increasing the capacity of officials, strengthening the oversight system, and improving operational service standards as strategic steps to achieve quality village public services based on legal certainty.